1999
DOI: 10.1038/sj.bjp.0702703
|View full text |Cite
|
Sign up to set email alerts
|

Active intestinal elimination of ciprofloxacin in rats: modulation by different substrates

Abstract: 1 Two in vivo models, in the rat, were used to investigate, in the presence of di erent substrates, the overall and net intestinal elimination of cipro¯oxacin: an open-intestinal perfusion model and an intestinal loop model respectively. 2 In the presence of quinidine, verapamil and cyclosporin (substrates of the P-glycoprotein (P-gp)), plasma AUCs of cipro¯oxacin were 1.5 ± 2 fold increased, while biliary clearance (1.5 ± 2 fold), intestinal overall and net clearances (2 ± 4 fold and 1.5 ± 8 fold respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…D Di is sc cu us ss si io on n In the present study, quinidine reduced the plasma concentration and increased the brain/plasma concentration ratio of bupivacaine at the onset of convulsions. Since quinidine inhibits P-gp activity at plasma concentrations lower than those used in the present study, 13,14 our results suggest that bupivacaine may be a substrate of P-gp and that inhibition of P-gp by quinidine increased the concentration of bupivacaine in the brain and reduced the plasma concentration of bupivacaine required to induce convulsions. Increased brain/plasma concentration ratio of P-gp substrates as observed in our study has also been reported in mice lacking P-gp compared with wild mice and in animals receiving P-gp inhibitors compared with those without P-gp inhibitors.…”
Section: Measurement Of Lidocaine Megx and Bupivacaine In Plasma Andmentioning
confidence: 79%
See 1 more Smart Citation
“…D Di is sc cu us ss si io on n In the present study, quinidine reduced the plasma concentration and increased the brain/plasma concentration ratio of bupivacaine at the onset of convulsions. Since quinidine inhibits P-gp activity at plasma concentrations lower than those used in the present study, 13,14 our results suggest that bupivacaine may be a substrate of P-gp and that inhibition of P-gp by quinidine increased the concentration of bupivacaine in the brain and reduced the plasma concentration of bupivacaine required to induce convulsions. Increased brain/plasma concentration ratio of P-gp substrates as observed in our study has also been reported in mice lacking P-gp compared with wild mice and in animals receiving P-gp inhibitors compared with those without P-gp inhibitors.…”
Section: Measurement Of Lidocaine Megx and Bupivacaine In Plasma Andmentioning
confidence: 79%
“…10,11 However, the effects of P-gp inducers or inhibitors on the CNS toxicity of local anesthetics remain unclear. Since local anesthetics are often used in combination with P-gp inhibitors such as verapamil, quinidine and cyclosporine, [12][13][14] examining the effect of P-gp inhibitors on the CNS toxicity of local anesthetics is important. In this study, we examined whether quinidine affects lidocaine-and bupivacaineinduced convulsions.…”
Section: Objectif : Vérifier Si L'inhibition De L'activité Des P-glycmentioning
confidence: 99%
“…Since conjugates of parent ivermectin have never been detected in bile, this study clearly demonstrates that the major route for the elimination of parent ivermectin in the rat intestine is not biliary but intestinal secretion. Such a difference between intestinal and biliary elimination has been already observed for other drugs such as roxithromycin (Arimori et al, 1998), ciprofloxacin (Dautrey et al, 1999), and vinblastine (Van Asperen et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Initially discovered in tumour cells while investigating the multidrug resistance mechanism, it has been also found and studied in many nontumour cells/tissues (Montano et al, 1996;Smit et al, 1998;Dautrey et al, 1999;Jonker et al, 1999;Gutmann et al, 2000;Florea et al, 2001;Batetta et al, 2003;Cisternino et al, 2003;Goralski et al, 2003;Elliott et al, 2004). P-gp indeed is involved in all pharmacokinetic events (Varma et al, 2003) and many single-nucleotide polymorphisms in the MDR1 gene have been correlated with differences in individual drug responsiveness (Marzolini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%